1983
DOI: 10.1121/1.389620
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysical studies evaluating the feasibility of a speech processing strategy for a multiple-channel cochlear implant

Abstract: This paper reports further psychophysical studies on a multiple-channel cochlear implant patient evaluating the feasibility of a speech processing strategy which converts the acoustic fundamental frequency to electric repetition rate, the second-formant frequency to electrode position, and the acoustic amplitude to current level. The first four studies evaluated the use of a special pulse pattern to minimize the loudness variation with electric repetition rate. The chosen pulse pattern consisted of multiple pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
92
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 11 publications
7
92
0
Order By: Relevance
“…The results of experiment 1 did demonstrate, however, that small concurrent place and rate changes can be combined by implantees in discrimination tasks, in a way consistent with the optimum processing of independent observations. The independence of place and rate cues is consistent with the earlier work of Tong et al, (1983).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of experiment 1 did demonstrate, however, that small concurrent place and rate changes can be combined by implantees in discrimination tasks, in a way consistent with the optimum processing of independent observations. The independence of place and rate cues is consistent with the earlier work of Tong et al, (1983).…”
Section: Discussionsupporting
confidence: 90%
“…Tong et al (1983) performed a multidimensional scaling study which indicated that electrode place and rate of stimulation were perceived in different dimensions. However, they used stimuli with large differences in place and temporal parameters and did not examine the perceptual capabilities at a difference-limen level.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the rate of stimulation from 100 pps up to about 600 pps produces increasingly higher pitch sensations, and this effect tends to asymptote at higher rates (Simmons et al 1979;Eddington 1980;Tong et al 1983;Townshend et al 1987;Busby and Clark 1997). In this study, stimulation rates were always higher than 700 pps and were held constant during the experiments.…”
Section: Discussionmentioning
confidence: 77%
“…Pitch sensations produced by multichannel cochlear implants have been extensively investigated in bilaterally deaf subjects using pitch-ranking experiments (Simmons et al 1979;Shannon 1983;Townshend et al 1987;Dorman et al 1990;Busby et al 1994;Nelson et al 1995;Collins et al 1997;Collins and Throckmorton, 2000) or pitch-estimation experiments (Eddington 1980;Tong et al 1983;Tong and Clark 1985;Shannon 1993;Busby et al 1994;Cohen et al 1996a;Busby and Clark 1997;Collins et al 1997). These studies demonstrated that electric stimulation of the ear produced complex auditory sensations, one component of which was similar to pitch.…”
Section: Introductionmentioning
confidence: 99%
“…Psychophysical studies have revealed that there are two basic cues for pitch perception in cochlear implant subjects (Tong et al 1982;Townshend et al 1987) and that these cues are independent of each other Tong et al 1983). The first cue is related to the site of excitation along the cochlea (place pitch).…”
Section: Introduction and Outlinementioning
confidence: 99%